2021
DOI: 10.3390/su13041924
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Energy Consumption, Economic Growth and Globalization in Environmental Degradation: Empirical Evidence from the BRICS Region

Abstract: This paper examines the effect of energy consumption, globalization, and economic growth on the CO2 emission of the BRICS (Brazil, Russian Federation, India, China and South Africa) region. Using annual data from 1989 to 2019, this research applies a panel cointegration approach. In this framework, we use Fully Modified Ordinary Least Squares (FMOLS) and Dynamic Ordinary Least Squares (DOLS) methods to examine the long-run relationship between the selected variables. This empirical investigation reveals that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 88 publications
2
23
0
3
Order By: Relevance
“…The authors of this study conclude that economic growth might affect the carbon emission of countries, but its magnitude may be different for different levels of economic development for each country. Similar studies are presented by Chontanawat [62] for Southeast Asian countries, by Leitao and Lorente [63] for European countries, by Rahman et al [64] for BRICS members, and by Kahia et al [65] for Saudi Arabia.…”
Section: Kasman Andsupporting
confidence: 77%
“…The authors of this study conclude that economic growth might affect the carbon emission of countries, but its magnitude may be different for different levels of economic development for each country. Similar studies are presented by Chontanawat [62] for Southeast Asian countries, by Leitao and Lorente [63] for European countries, by Rahman et al [64] for BRICS members, and by Kahia et al [65] for Saudi Arabia.…”
Section: Kasman Andsupporting
confidence: 77%
“…The effects of energy consumption, economic growth and globalization on carbon dioxide emissions for BRICS (Brazil, Russia, India, China, and South Africa) economies were considered by Rahman et al (2021). The authors applied panel data (FMOLS (panel fully modified least squares) and DOLS (panel dynamic ordinary least squares)) for 1989-2019.…”
Section: Economic Growth International Trade and Climate Changementioning
confidence: 99%
“…Some research has paid attention to the correlation between carbon emissions and economic growth, energy consumption and other factors in BRICS countries. Some studies argued that globalization increases pollution indicators [14,15]. Wu et al [16] found that for BRICS countries, the carbon emissions of Brazil and Russia descended with economic growth.…”
Section: Study On the Impact Of Economic Growth On Carbon Emissionsmentioning
confidence: 99%